Odróżniać czy upodabniać? Trzy polskie przekłady „The Book of the Lost Tales” J.R.R. Tolkiena a „Silmarillion” w tłumaczeniu Marii Skibniewskiej (na materiale rozdziału „The Music of the Ainur”) - Agnieszka Żurek (Literatura i Kultura Popularna)
The Book of the Lost Tales (1983–1984) by J.R.R. Tolkien was translated into Polish three times: by Magdalena Pietrzak-Merta (1995–1996), by Radosław Kot (1998) and by Maria and Cezary Frąc and Agnieszka Sylwanowicz (2022–2023). The chapter ‘The Music of the Ainur’ bears significant resemblance to the later version published in The Silmarillion (1977), which includes numerous similar or even identical phrases. Radosław Kot explains in a footnote he decided to reproduce the identical phrases from Maria Skibniewska’s translation of The Silmarillion (1985). That technique was used also by Magdalena Pietrzak-Merta and Maria and Cezary Frąc, though the number and length of repeated phrases is different. It allows to reproduce the experience of the reader of the source text who is able to trace unmodified fragments. However, sometimes the translators ignore the differences between The Book of the Lost Tales and The Silmarillion, therefore the target text presents as a translation of The Silmarillion rather than The Book of the Lost Tales. The technique manifests central position of Maria Skibniewska’s works in the system of Polish translations of the legendarium.